Mesoscopic simulation model of the logistics system of concentrated sets of urban delivery locations. (22nd June 2021) - Sárdi, Dávid Lajos; Bóna, Krisztián
In city logistics, the examination of the urban concentrated sets of delivery locations is an important, new area. In these sets, there are a relatively large number of stores with significant goods traffic, which generates significant customer traffic, while their logistics systems are not properly designed. Despite all this, city logistics research projects do not specifically target this field. Earlier, only a few subsystems have been examined, so we started to study and model the concentrated sets of delivery locations generally. In our research, such a mesoscopic level mathematical and a simulation model was developed in MS Excel, which can clearly show the performances and the costs in the current city logistics system, and the possible savings in case of new, consolidation-based city logistics systems of the concentrated sets of delivery locations. Based on the results of the simulation runs performed by this model, it is clear that the performances and the emissions can be significantly reduced in the new systems, and the logistics costs of the new system will be less too. Additionally, this simulation model can be applied for the sizing of the city logistics junctions of the new systems and for ranking of these sets too.